Pengelompokan Seleksi Siswa Baru di Lembaga Pendidikan Non Formal Kabupaten Gresik Menggunakan Clustering K-Medoids - Nia Saurina; Lestari Retnawati; Firman Hadi Sukma Pratama; Udik Pudjianto (Jurnal Sains dan Informatika, 2023)
Non-formal education has different programs according to the current and future needs of society. The course institutions in Gresik Regency are the unofficial educational institutions of the Gresik Regency Education Office which organize programs, namely the SMA Package C Equivalency Education Program, the SMP Package B Equality Education Program and the Sewing Course. The current grouping of new student selection is felt to be less effective because the grouping is based on certificates obtained more than two years ago. This is because most non-formal students drop out of school due to financial constraints. So that the value given to the certificate is not in accordance with the qualifications of students while taking informal education. This study uses the K-Medoids cluster using datasets, namely practical exam scores, final exam scores and interview scores. The data used are students enrolled in package C as high school equivalents as many as 28 students and 32 students enrolled in package B as high school equivalents. The results obtained in this study are educational institutions that can place prospective students at a more accurate value. The Medoid-K clustering procedure for new student clustering requires two iterations to get a total S-distance of 54.594255.